THE ANALYSIS OF EDUCATION VALUE IN BAD GENIUS MOVIE - Devi Tri Romadhoni; Fiona Puspitasari Mulyadi; Beta Setiawati (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2021)
This article provides the educational meaning of the Bad Genius movie. This study aims to provide an analysis and understanding of educational values in the Bad Genius movie. Our research method uses a qualitative descriptive approach. The results of this study indicate that the values of character education in the Bad Genius film are very useful and can have a positive impact in the field of education. There are 5 cultural values namely :honest, peace of ability, self - discipline, love & affection, respect, kindness & friendliness.